KECENDERUNGAN PENGGUNAAN HUKUM ADAT DAN EFEKTIVITAS PENGENAAN SANKSI ADAT TERHADAP TINDAK PIDANA PERZINAHAN DI DESA TODANARA KECAMATAN ILE APE TIMUR KABUPATEN LEMBATA - Making, Philadelfianus J. O; Medan, Karolus Kopong; Amalo, Heryanto (Petitum Law Journal, 2023)
Customary law plays a role in shaping society to interact properly and correctly as well as as a means of anticipating social clashes that result in conflict. The existence of customary law in society is a reflection of community life and each region has different customary laws according to the customs existing in that area with characteristics that are not written or codified. Likewise in Lembata district, especially in Todanara village, in addition to the enactment of the Criminal Code as an umbrella for criminal law, there is also evidence in certain aspects of community life of the application of criminal customary law in the form of sanctions in the form of fines and exclusion from social circles. visible in social life. Problem formulation: 1. Why do Todanara village communities tend to resolve adultery cases through customary legal mechanisms, 2. How effective is the imposition of customary sanctions against criminal acts of adultery in Todanara village, East Ile Ape District, Lembata Regency? This research aims to find out, analyze and explain the reasons or causes of society using customary law and resolving adultery cases through customary law mechanisms as well as knowing and analyzing the effectiveness of the imposition of customary sanctions against the crime of adultery in Todanara Village, Ile Ape Timur District, Lembata Regency The research method used in this thesis uses empirical juridical research methods or field research. Results of research on trends in the use of customary law and the effectiveness of the imposition of customary sanctions against acts of adultery in Todanara Village, Ile Ape Timur District, Lembata Regency, the community still upholds cultural values ​​that bind communities to one another within the framework of family harmonization. The community also maintains family integrity so that it uses customary law as a persuasive approach to maintain broken social relations. The suggestion is that the government of Todanara Village, Ile Ape District, Lembata Regency can play an active role in increasing legal awareness through socialization and legal counseling to create a community that is aware of the law and that traditional leaders create a consensus with the community to create customary law with binding force so that it has a deterrent effect. for perpetrators of criminal acts of adultery and in applying customary sanctions, traditional leaders must reaffirm the customary rules that have been agreed upon, then provide customary sanctions that can minimize cases of adultery.